Does Partnering Pay Off? - Stock Market Reactions to Inter-Firm Collaboration Announcements in Germany - Carolin Häussler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
The dramatic increase in interorganizational partnering in the last two decades raises questions for scholars and managers regarding the value impact of inter-firm collaborations. Using event study methodology, this paper tests whether stock market reactions differ when a collaboration formation or termination is announced. In addition, the study provides an in-depth analysis of potential determinants of stock market reactions to collaboration formation announcements. The sample consists of 1037 announcements in German stock markets from 1997 to 2002. The results show that an unexpected termination announcement decreases firm valuation, and a formation announcement increases firm valuation. Further, certain collaborations are more favorable than others, depending on firm industry, age, size, collaboration constellations, and equity versus non-equity investment in partner firm. The results open avenues for further research on partnering strategies.
urn:nbn:de:bvb:19-epub-13534-5
Keywords: 330